The Role of Internal Audit in ESG Disclosure and Sustainability Reporting: A Qualitative Study Based on Public Document Analysis of Indonesian Companies - Denny Prayitno; Jayanti Budiman (Journal of Sharia Economics, Banking and Accounting, 2026)
OJK Regulation No. 51/POJK.03/2017 has substantially expanded the volume of non-financial reporting among Indonesian companies, yet a more fundamental question lies beneath this growth: who actually ensures that the ESG information disclosed in these reports is reliable? This study departs from that concern by placing the Internal Audit function at the center of analysis. Drawing on a qualitative, document-based approach — examining Annual Reports, Sustainability Reports, Internal Audit Charters, and GCG Reports from eight purposively selected companies across state-owned enterprises and firms listed on the Indonesia Stock Exchange during the 2022–2023 period — the study identifies three roles performed by Internal Audit: assurer of ESG data accuracy, advisor in the design of sustainability-related internal controls, and monitor of compliance with OJK Regulation No. 51/POJK.03/2017. The analysis indicates that the depth of Internal Audit involvement tends to correspond with the quality and comprehensiveness of ESG disclosure, although this relationship should be read as an observed pattern rather than a confirmed causal link. The study contributes to a broader understanding of Internal Audit’s strategic function beyond conventional financial auditing, and offers grounded arguments for regulators seeking to strengthen the position of Internal Audit within Indonesia’s sustainability reporting ecosystem.